TRANSPARENCY REPORTS AND AUDIT MARKET ANALYSIS IN THE REPUBLIC OF NORTH MACEDONIA - Malchev, Bojan; Bozhinovska Lazarevska, Zorica; Dionisijev, Ivan; Tocev, Todor; Atanasovski, Atanasko (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
Transparency reports are a communication link between audit firms and the general public about their work, internal policies, and quality control to increase the trust of information users. On the other hand, the need for transparency in audit firms is a factor that aims to substantially improve and maintain the quality of audits at the highest level. This paper is quantitative and qualitative research on the transparency of audit firms in the Republic of North Macedonia and analysis of the financial data contained in them, focusing on the audit firms' revenue. Through a detailed elaboration of each audit firm’s transparency reports in the period from 2007 to 2021, or a total of 372 individual transparency reports, we identified the state of transparency reports that differs in the period from 2007 to 2013 versus 2014 to 2021, positive trends of financial indicators over the years, as well as the structure of total revenues, i.e. participation of the individual services they offer. The hypothesis testing findings are early results, identifying the positive correlation between the number of employees and the audit-related turnover regardless of the audit firms' size and their affiliation with Big 4, an international network, or local audit firms. Between the number of customers, i.e. audit engagements and the audit-related turnover, there is a positive correlation for international network audit firms and local audit firms, but not for the Big 4. The paper contributes to the current literature on audit firms’ transparency in order to improve them and their real contribution to improving the quality of audit engagements. The results of the conducted quantitative analysis are a good basis for further in-depth research in identifying potential factors that correlate with the audit firms’ revenue.
Keywords: Transparency report, Audit, Audit firms revenues, Republic of North Macedonia